Hybrid Construction - Timber External Walls : Hybrid design: eco-efficient + economic - Fischer, Oliver (DETAIL Praxis, 2022)
Hybrid construction of reinforced concrete and wood combine the advantages of solid construction with those of wood construction and thus represent an optimal construction option. Wood is eco-efficient and high degrees of prefabrication ensure an upscale quality standard and enable implementation without scaffolding, which in turn promises economic benefits. Concrete offers proven and cost-effective supporting structures for all building classes with common concepts of building technology and fire and sound insulation.The publication shows detailed solutions for the successful implementation of structural engineering and building physics requirements for hybrid construction, especially with regard to noise and fire protection. Project examples document comprehensively the successful implementation in practice.